The effectiveness of peer instruction and structured inquiry on conceptual understanding of force and motion: A case study from Thailand - Suppapittayaporn,D. (Taylor and Francis Ltd., 2015)
This study proposed to investigate the effectiveness of learning activities based on a conceptual change theoretical framework by embedding a peer instruction method with structured inquiry (PISI) on tenth grade students' understanding of force and motion concepts. This teaching method was compared to the existing traditional instruction (TI). Alternative conceptions of force and motion were determined through related literature and a preliminary study, carried out prior to instruction, was used for designing the teaching plans. A standardized test, Force and Motion Conceptual Evaluation (FMCE), was used to probe students' conceptual understanding of the subject. The data were obtained from 156 students in the treatment group taught with the PISI and 119 students in the control group taught with the TI. Hake's normalized gain indicated that the effectiveness of the TI was low (0.14) while the effectiveness of the PISI was medium (0.45). The Repeated Measures ANOVA comparing the pre- and post-test change in each and overall scales of the FMCE between the two groups was significant (p<0.01). The results suggested that teachers with a similar school setting could adopt the PISI into their classroom in order to promote the learning of physics with conceptual understanding of the subject. © 2010 Taylor & Francis.